(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2020)
The main directions of implementation of audit functions in order to improve the system of tax policy (tax accounting, planning, counter) in the newly formed sectoral and territorial (administrative) clusters, namely agricultural holdings, united territorial communities are studied. It is established that the planning of sectoral clusters is conditioned by measures to economically stimulate enterprises in the industry or regulate its functioning through the mechanism of grants, compensations, subventions, tax policy transformation in terms of tax accounting and planning, implementation of state or local programs with appropriate funding. It is proved that the amount and methods of financing the development of agriculture is determined through the mechanism of formation and implementation of the budget program, in connection with which there is a need to adequately assess the prospects for its full and timely implementation. In view of this, it is possible to state the need for the subjects of state control to perform audit measures, the implementation of which should result in an assessment of the indicators of the program and the possibility of its implementation in a timely manner. It is proposed to use a risk-oriented approach in planning activities to audit the activities of enterprises, the subjects of state control ensure the effective use of their own limited resources, which helps to optimize the costs associated with financing their work. The existence of established criteria for deciding on audits and other forms of control based on the existence of risks in the activities of controlled objects allows to identify possible deviations, the content of which, in accordance with applicable law may be classified as a violation.